VOLCANIC HAZARDS IN THE REGION OF THE ARMENIAN NUCLEAR POWER PLANT - Karakhanian A.; Arakelian S.; Avagyan A.; Baghdassaryan H.; Davtian V.; Jrbashyan R.; Ghoukassyan Yu.; Trifonov V.; Philip H. (My University, 2003)
We address volcanic hazards in the region of the Armenian Nuclear Power Plant and discuss the assessment of these hazards conducted in the framework of the International Atomic Energy Agency (IAEA) programs in 1994–1995. An important problem of volcanic hazard assessment is posed by assumptions that the apparent absence of recent volcanic activity in Armenia means that future eruptions in the vicinity of the site are impossible. We present new historical, archaeological, and field data, as well as records of the volcanic activity based on radiocarbon, fission-track, K/Ar and plateau-age determinations. This new evidence attests to volcanism in Armenia and adjacent areas during Holocene and historical time. Volcanic activity is demonstrated for Tskhouk-Karckar, Porak, Vaiyots-Sar, Smbatassar, Gegham Ridge and Ararat volcanoes. Volcanic eruptions occurred on Ararat at distances of 27 and 52 km from the plant site in 2500–2400 BC and in 1840 AD, respectively. New information permits a re-assessment of the volcanic hazards at a level higher than in the 1994–1995 studies.
Keywords: volcanic hazard; Armenian Nuclear Power Plant; Armenia